Impact of wealth inequality on child nutrition in Bangladesh - Mortuza Ahmmed (Indonesian Pediatric Society Publishing House, 2013)
Background The prevalence of malnutrition in Bangladesh is among the highest in the world. Millions of women and children suffer from one or more forms of main utrition, including low birth weight, wasting, stunting, underweight, vitamin A deficiency, iodine deficiency disorders, and anemia. Today malnutrition not only affects individuals, but its effects are passed from one generation to the next as malnourished mothers give birth to infants wh o struggle to develop and thrive. Objective To assess the economic impact on child nutrition in Bangladesh. Methods The 2011 Bangladesh Demographic Health Survey data was used for this study. In this study, quintiles were calculated based on asset and wealth scores by use of principal component analysis. To understand the nutritional status and health inequality, concentration index was also calculated. Results The negative concentration index showed a higher rate of malnutrition in the children less than five years of age from the poorest class. Furthermore, the ratio of poorest to richest indicated that stunting and underweight conditions in rural children under five years of age were almost two times higher than that of the richest children. This inequality in the health situation of children may be explained in terms of income inequality. In Bangladesh, about 40% of the wealth is concentrated in 10% of the families. The results are discussed as possible input for public policy. Conclusion Bangladeshi children under the age of five years and in the poorest economic class are nearly twice as likely to be underweight or stunted compared to children of similar age in the richest economic class